2013
DOI: 10.1002/biof.1072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of hypolipidemic effects of curcumin

Abstract: Recent evidence suggests potential benefits from phytochemicals and micronutrients in reducing the elevated oxidative and lipid-mediated stress associated with inflammation, obesity, and atherosclerosis. These compounds may either directly scavenge reactive oxygen or nitrogen species or they may modulate the activity of signal transduction enzymes leading to changes in the expression of antioxidant genes. Alternatively, they may reduce plasma lipid levels by modulating lipid metabolic genes in tissues and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 238 publications
3
111
0
Order By: Relevance
“…This observation is consistent with previous findings that curcumin treatment inhibits lipid-induced ER stress 14 and diabetes-induced ER stress in the adult heart 27 . In our previous studies, we have elucidated a critical role of ER stress in hyperglycemia-induced NTD formation 20, 28 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is consistent with previous findings that curcumin treatment inhibits lipid-induced ER stress 14 and diabetes-induced ER stress in the adult heart 27 . In our previous studies, we have elucidated a critical role of ER stress in hyperglycemia-induced NTD formation 20, 28 .…”
Section: Resultssupporting
confidence: 94%
“…Curcumin is a potent antioxidant which has been shown to suppress diabetes-induced superoxide in vascular endothelial cells 13 . In addition to its antioxidant properties, curcumin appears to be able to modulate signal transduction and gene expression 14 . A previous study has demonstrated that curcumin blocks diabetes-induced inducible nitric oxide synthase (iNOS) expression in the adult heart 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, curcumin is also commonly used as a coloring and flavoring additive in foods. Recent studies indicate that dietary administration of curcumin may be effective in treating conditions such as cancer, Alzheimer disease, and cystic fibrosis (14,15). With regards to the mode of action, curcumin exerts a rather diverse array of metabolic, cellular, and molecular activities (15).…”
mentioning
confidence: 99%
“…Recent studies indicate that dietary administration of curcumin may be effective in treating conditions such as cancer, Alzheimer disease, and cystic fibrosis (14,15). With regards to the mode of action, curcumin exerts a rather diverse array of metabolic, cellular, and molecular activities (15). However, certain pharmacokinetic defects, such as low bioavailability and fast metabolism, and poor chemical stability significantly limit the clinical application of curcumin.…”
mentioning
confidence: 99%
“…However, recent research has suggested that the effects of curcumin at lower concentrations which are achieved in vivo are independent of its antioxidant properties and are via signal transduction and gene expression. 257,258 Indeed, treatment was associated with changes in the gene expression of proteins involved in fatty acid oxidation. Of interest, the gene expression of AdipoR2 was attenuated in Hfe -/-mice fed a HFD consistent with previous observations.…”
Section: Mdr2mentioning
confidence: 99%